The Risk of Exposure to Cigarette Smoke in Anemia During Pregnancy - Safitri, Riska Nur; Syahrul, Fariani (Jurnal Berkala Epidemiologi, 2015)
ABSTRACTAnemia is a state of hemoglobin levels in the RBC (Red Blood Cells) are lower than normal according to age and gender. The prevalence of anemia during pregnancy according Riskesdas 2007,2010, and 2013 tend to increase. One of risk factor isenvironmental tobacco smoke (ETS). This research was study the comparative risk of ETS exposure of anemia in pregnant woman. This study used case control design. Research sample consisted of two groups, case and control sample with the comparative at 1:2. Sample cases were pregnant women anemia (n=18) who control in Puskesmas Mojo Surabaya on 2015 while samplescontrol were pregnant woman who did not anemia (n=36), collected by simple random sampling. to determine the influence of risk by calculating the value on OR 95% CI with Statcalc in Epi Info. The independent variables were age, education level, employement status, family income, gestational age, gestational spacing, history of pregnant double, parity, antenatal care (ANC), LILA, Fe tablets. Results showed the risk exposure to ETS on the incidence of anemia in pregnant woma to the OR = 4.09 (1.07 < OR < 16.26), time of beginning the exposure 1st trimester OR = 5.43 (1.12< OR < 34.41), the number of active smokers 1-2 OR = 5.54 (1.20 < OR < 34.28), exposure duration â¤ 15 minute/day OR = 6.33 (1.28 < OR < 40.53).The conclusion is the exposure to cigarette smoke can causeanemia in pregnant woman. It is recommended for pregnant woman to avoid ETS exposure during pregnancy.Keywords: anemia, pregnant woman, environmental tobacco smoke (ETS), number of smoker, exposure duration